Integrated membrane electrochemical reactor-membrane distillation process for enhanced landfill leachate treatment. (15th February 2023) - Yan, Zhongsen; Zhu, Zhengshi; Chang, Haiqing; Fan, Gongduan; Wang, Qiankun; Fu, Xianzhi; Qu, Fangshu; Liang, Heng
Highlight: Hybrid MER and MD was firstly developed for LFL treatment. MER removed 61% hardness and recovered 31 % of ammonia nitrogen and 48% of HA in LFL. MD membrane fouling reversibility was significantly improved with MER pretreatment. MER pretreatment reduce ∼20% energy consumption and carbon emission in the MD treatment. Abstract: Treatment of recalcitrant landfill leachate (LFL) induces huge energy consumption and carbon emissions due to its complex composition. Although membrane distillation (MD) exhibits good potential in LFL treatment with waste heat utilization, membrane fouling and ammonia rejection are still the major problems encountered that hinder its application. Herein, membrane electrochemical reactor (MER) was coupled with MD for simultaneous membrane fouling control and resource recovery. LFL pretreatment with membrane-less electrochemical reactor (EO) and without pretreatment were also purified by MD for comparison. Results showed that the MER-MD system rejected almost all CODCr, total phosphorus, metal salts, and ammonia nitrogen (increased by 33.5%–43.5% without chemical addition), and recovered 31% of ammonia nitrogen and 48% of humic acid in the raw LFL. Owing to the effective removal of hardness (61%) and organics (77%) using MER, the MER-MD system showed higher resistance to the membrane wetting and fouling, with about 61% and 14% higher final vapor flux than those of the MD and EO-MD systems, respectively, and the pure water flux could be fully recovered by alkaline solution cleaning. Moreover, SEM-EDS, ATR-FTIR and XRD characterization further demonstrated the superiority of the MD membrane fouling reversibility of the MER-MD system. Energy consumption and carbon emissions analysis showed that the MER-MD system reduced the total energy consumption/carbon emissions by ∼20% and ∼8% compared to the MD and EO-MD systems, respectively, and the ammonia nitrogen recovered by MER could offset 8.25 kg carbon dioxide equivalent. Therefore, the introduction of MER pretreatment in MD process would be an option to decrease energy consumption and reduce carbon emissions for MD treatment of LFL. Graphical abstract: Image, graphical abstract